2014
DOI: 10.4049/jimmunol.1300337
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Ssbp2 in Hematopoietic Stem Cell Maintenance and Stress Response

Abstract: Transcriptional mechanisms governing hematopoietic stem cell (HSC) quiescence, self-renewal, and differentiation are not fully understood. Sequence-specific single-stranded DNA-binding protein 2 (SSBP2) is a candidate acute myelogenous leukemia (AML) suppressor gene located at chromosome 5q14. SSBP2 binds the transcriptional adaptor protein Lim-domain binding protein 1 (LDB1) and enhances LDB1 stability to regulate gene expression. Notably, Ldb1 is essential for HSC specification during early development and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…SSBP2 has a critical regulatory role in the transcriptional program of hematopoietic stem and progenitor cells in vivo , via modulating the abundance and function of multiple transcription cofactors including LIM domain-binding protein 1 (LDB1), LMO, and LHX. In mouse models, loss of SSBP2 resulted in hypoplastic hematopoietic tissues and impaired hematopoiesis and was associated with shortened lifespan and greater susceptibility to B-cell lymphomas [34, 35, 48]. Prognostic significance of CD5 expression in SSBP2 + and SSBP2 − DLBCL patients also suggests a tumor-suppressor function of SSBP2 for CD5 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…SSBP2 has a critical regulatory role in the transcriptional program of hematopoietic stem and progenitor cells in vivo , via modulating the abundance and function of multiple transcription cofactors including LIM domain-binding protein 1 (LDB1), LMO, and LHX. In mouse models, loss of SSBP2 resulted in hypoplastic hematopoietic tissues and impaired hematopoiesis and was associated with shortened lifespan and greater susceptibility to B-cell lymphomas [34, 35, 48]. Prognostic significance of CD5 expression in SSBP2 + and SSBP2 − DLBCL patients also suggests a tumor-suppressor function of SSBP2 for CD5 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…One of the known functions of SSBP2 is to bind LDB1 and regulate LDB1 activity. LDB1 regulates the differentiation of luminal cells in the gastrointestinal tract [ 17 ] and cardiomyocytes [ 18 ] and is also involved in cancer progression [ 11 , 19 ]. Several studies on the promoter methylation of SSBP2 in tumors have shown that it is one of the genes downregulated by methylation [ 13 15 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single-stranded DNA binding protein 2 (SSBP2) is known to be a candidate tumor suppressor in patients with myeloid leukemia located at chromosome 5q14 [ 8 10 ]. SSBP2 binds to the transcriptional cofactor Lim-domain-binding protein 1 (LDB1) and enhances LDB1 stability to regulate gene expression [ 11 ]. The role of SSBP2 has also been studied in several solid tumors including hepatocellular carcinoma, gallbladder cancer, esophageal squamous cell carcinoma, and prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…LMO2 [51], LDB1 [52], and SSBP2 [53] are required for the function or maintenance of hematopoietic stem cells, and Ldb1 has also been shown to be essential to the survival of intestinal epithelial stem cells [54]. As the malignant counterparts of these cells have been found in a number of epithelial neoplasms, including HNSCC (reviewed in [55]) and have been implicated in metastasis [56, 57], tumor angiogenesis [58], and lymphangiogenesis [59] (see below), we speculate that LIM-only, LIM domain-binding, and single-stranded DNA-binding proteins regulate both normal and cancer stem cells.…”
Section: Discussionmentioning
confidence: 99%